2019
DOI: 10.1111/cns.13136
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin A‐activated autophagy but not mitophagy protects against ischemic neuronal injury by inhibiting ER stress in vitro and in vivo

Abstract: Aim Mitochondrial autophagy (mitophagy) clears damaged mitochondria and attenuates ischemic neuronal injury. Urolithin A (Uro‐A) activates mitophagy in mammal cells and Caenorhabditis elegans. We explored neuroprotection of Uro‐A against ischemic neuronal injury. Methods Mice were subjected to middle cerebral artery occlusion. The brain infarct and neurological deficit scores were measured. The N2a cells and primary cultured mice cortical neurons were subjected to oxygen‐glucose deprivation and reperfusion (OG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 48 publications
5
51
1
Order By: Relevance
“…This finding is in agreement with the previously reported lower neuronal loss observed in rats with I/R injury pretreated with punicalagin [43]. Interestingly, the systemic administration of its metabolite UA has protected mice against ischemic brain injury that correlated with an improved neurological deficit score [44]. Based on this, it seems likely that urolithin A could contribute to the protective effect of PJ-treatment against rotenone-induced neuronal degeneration which results in behavioral improvement.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with the previously reported lower neuronal loss observed in rats with I/R injury pretreated with punicalagin [43]. Interestingly, the systemic administration of its metabolite UA has protected mice against ischemic brain injury that correlated with an improved neurological deficit score [44]. Based on this, it seems likely that urolithin A could contribute to the protective effect of PJ-treatment against rotenone-induced neuronal degeneration which results in behavioral improvement.…”
Section: Discussionsupporting
confidence: 92%
“…Neuro-2a is a neuroblastoma cell line derived from mice, which has been used because of its ability to produce microtubular proteins. Few works have been done with urolithins using this cell line, but it has been demonstrated that urolithin A protects against ischemic neuronal injury by activating autophagy [29]. This research supports our results on mitochondrial activity, demonstrating that urolithin A is not cytotoxic at this range of physiological concentrations (0.5-50 μM).…”
Section: Discussionsupporting
confidence: 90%
“…It has been recently shown to have a pleotropic role in the CNS including activation of inflammation, induction of scar formation, promotion of cognitive decline and inhibition of repair [20,21]. Mitochondrial import membrane translocases have an implied role in several neurological disease conditions [22][23][24][25][26]. Another protein found exclusively on the CMD membrane was Aldo-keto reductase 1C2 (AKR1C2) shown previously to be increased in the late stages of Alzheimers Disease [27].…”
Section: Discussionmentioning
confidence: 99%